2018
DOI: 10.1371/journal.pone.0194069
|View full text |Cite
|
Sign up to set email alerts
|

Berberrubine attenuates mucosal lesions and inflammation in dextran sodium sulfate-induced colitis in mice

Abstract: Ulcerative colitis (UC) is a chronic relapsing disease without satisfactory treatments, in which intestinal inflammation and disrupted intestinal epithelial barrier are two main pathogeneses triggering UC. Berberrubine (BB) is deemed as one of the major active metabolite of berberine (BBR), a naturally-occurring isoquinoline alkaloid with appreciable anti-UC effect. This study aimed to comparatively investigate the therapeutic effects of BB and BBR on dextran sodium sulfate (DSS)-induced mouse colitis model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 55 publications
(63 reference statements)
7
41
0
Order By: Relevance
“…Instead, idebenone significantly improved the body weight, DAI and histopathology. Our results support the previously reported involvement of oxidative stress in the pathogenesis of disease [15] and justify the use of antioxidants to alleviate structural tissue damage [19,27,46,47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Instead, idebenone significantly improved the body weight, DAI and histopathology. Our results support the previously reported involvement of oxidative stress in the pathogenesis of disease [15] and justify the use of antioxidants to alleviate structural tissue damage [19,27,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that the anti-inflammatory cytokine IL-10 is elevated in colitis patients [47,[82][83][84][85][86]] and our study mirrored this effect upon DSS exposure. Elevated levels of IL-10 could be interpreted as a compensatory mechanism to counteract the substantial inflammation in the colon.…”
Section: Discussionsupporting
confidence: 84%
“…Gut barrier typically consists of colonocyte plasma membrane tight junctions, secreted mucus, and mucosal immune cells [ 13 ]. It is reported that the destruction of the tight junctions is one possible mechanism for the breached gut barrier in DSS-treated mice [ 11 ] and a variety of phytochemicals, such as naringenin from citrus fruits and berberrubine from berberis, are reported to upregulate tight junction proteins in DSS-treated mice [ 29 , 30 ]. To investigate whether protection by RB and CB against increased gut permeability is through effects on tight junctions, mRNA expression of genes involved in the production of tight junction proteins, as well as protein expression of two tight junction proteins was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicine from plants has been used in healing various diseases owing to its long history in clinical practice as well as therapeutic effects [10,11]. Recently, the protection effects of Xuanfudaizhetang has been proved in rats with RE via increasing the pH value of the esophagus and reducing inflammation stimulation [7].…”
Section: Introductionmentioning
confidence: 99%